Improving the performance of the MIMO-OFDM-NOMA System using a V-BLAST ZF approach based on deep CNN in IoT - Mehdi Izadi; Gholam-Reza Mohammad-Khani; Gholamreza Farahani (EURASIP Journal on Wireless Communications and Networking)
Abstract We are heading toward an “everything, everywhere, and always connected” future, and the IoT will become a key part of our future lives. To achieve this goal, high-efficiency communication networks capable of handling high-rate data transmissions are required. In this paper, the network performance of the MIMO-OFDM-NOMA system was evaluated based on user location estimation by a deep CNN and channel estimation using the V-BLAST ZF technique. The results showed that the proposed method improved communication performance by approximately 9.59%, energy efficiency by 23.53%, and throughput by about 53.71% compared to the MMSE technique. Additionally, to examine the impact of using NOMA, BER and delay metrics were used. The results showed that by using the V-BLAST ZF technique, the BER for the MIMO-OFDM-NOMA network would be approximately 70.9% better than the MIMO-OFDM. Furthermore, the delay would be reduced by 21.29%.